2002
DOI: 10.1021/jp020625e
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Thermal Decomposition of 2-Azidoethanol and 2-Azidoethyl Acetate by Ultraviolet Photoelectron Spectroscopy and Matrix Isolation Infrared Spectroscopy

Abstract: The thermal decompositions of 2-azidoethanol and 2-azidoethyl acetate have been studied by matrix isolation infrared spectroscopy and real-time ultraviolet photoelectron spectroscopy. The products that were detected in a flow system at different temperatures (CH2NH, H2CO, N2, CO, and HCN from N3CH2CH2OH and C2H4, CH2NH, HCN, CO2, and N2 from N3CH2COOCH2CH3) allowed mechanisms for decomposition to be proposed. The experimental evidence obtained is consistent with 2-azidoethyl actetate decomposing via a concerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…Detailed kinetic models on decomposition of EA included these species [23,24]. (CH 2 =NH) is the simplest imine compound, it has been observed in the pyrolysis of methylamine, ethylamine (amines in general), and azides as a reactive intermediate [25][26][27][28][29][30][31][32][33]. A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed kinetic models on decomposition of EA included these species [23,24]. (CH 2 =NH) is the simplest imine compound, it has been observed in the pyrolysis of methylamine, ethylamine (amines in general), and azides as a reactive intermediate [25][26][27][28][29][30][31][32][33]. A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…(CH 2 =NH) is the simplest imine compound, it has been observed in the pyrolysis of methylamine, ethylamine (amines in general), and azides as a reactive intermediate [25][26][27][28][29][30][31][32][33]. A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. As a reactive species, MI can dissociate by 1,2-elimination of H 2 which has been studied both experimentally and theoretically [44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [1][2][3] on the thermal decomposition on organic azides by photoelectron spectroscopy (PES) and infrared matrix isolation spectroscopy have shown that two distinct decomposition pathways must be invoked to account for the experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…It was first recognised in the decomposition of azidoacetic acid [1] (Scheme 2) and has subsequently also been found to occur in the pyrolysis of ethyl azidoacetate. [3] In both these molecules, "Type 1" behavior is also possible, but is evidently less favorable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation